Air quality indicators from the Environmental Performance Index: potential use and limitations in South Africa - Garland, R.M; Naidoo, M; Sibiya, B; Oosthuizen, R (Clean Air Journal, 2017)
In responding to deteriorating air quality, many countries, including South Africa, have implemented national programmes that aim to manage and regulate ambient air quality, and the emissions of air pollutants. One aspect within these management strategies is effective communication to stakeholders, including the general public, with regard to the state and trend of ambient air quality in South Africa. Currently, information on ambient air quality is communicated through ambient mass concentration values, as well as number of exceedances of South African National Ambient Standards. However, these do not directly communicate the potential impact on human health and the ecosystem. To this end, the use of air quality indicators is seen as a potential way to achieve communication to stakeholders in a simplified, yet scientifically defensible manner. Air quality indicators and their source data from the Environmental Performance Index (EPI) were interrogated to understand their potential use in South Africa. An assessment of four air quality indicators, together with their source data, showed improvements in air quality over the time period studied, though the input data do have uncertainties. The source data for the PM indicators, which came from a global dataset, underestimated the annual PM2.5 concentrations in the Highveld Priority Area and Vaal Triangle Airshed Priority Area over the time period studied (2009-2014) by 3.7 times. This highlights a key limitation of national-scale indicators and input data, that while the data used by the EPI are a well-thought out estimate of a country’s air quality profile, they remain a generalised estimate. The assumptions and uncertainty inherent in such an ambitious global-wide attempt make the estimates inaccurate for countries without proper emissions tracking and accounting and few monitoring stations, such as South Africa. Thus, the inputs and resultant indicators should be used with caution until such a time that local and ground-truthed data and inputs can be utilised.